SIFAT FISIK DAN ORGANOLEPTIK NUGGET YANG DIBUAT DENGAN DAGING KELINCI YANG BERBEDA - Nunu Nuraeni; Efrilia Tri Wahyu Utami; Eko Priyono; Wahid Mustofa Mustofa (JURNAL SAINS PETERNAKAN NUSANTARA, 2023)
This study aims to determine the physical and organoleptic properties of nuggets made from different rabbit meat. This research was conducted from 1 February to 31 March 2022 in Bendogarap Village, Klirong District, Kebumen Regency, Central Java and UMNU Kebumen campus. The rabbit meat used was Rex, and New Zealand. Data obtained in the organoleptic test in the form of aroma, taste, texture, and hardness of rabbit meat nuggets were analysed by nonparametric test (Kruskal Wallis Test). Physical properties data in the form of pH values obtained will be analysed using Independent-Sample T Test analysis of variance. The results of this study are different types of rabbit meat showed that it was not significantly different (P>0.05) to the pH value, the level of taste preference, texture, and hardness of the nuggets. However, it had a significant effect (P<0.05) on the level of favourability of nugget aroma. The pH value produced in both types of rabbit meat tends to be the same. new zealand meat type is more preferred than rex in the organoleptic test of aroma, taste, texture and hardness of nuggets. Keywords: nuggets, physical properties, organoleptic, rex, new zealand